2017
DOI: 10.1007/s10741-017-9666-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anti-hyperglycemic drug therapy on cardiovascular and heart failure outcomes in patients with type 2 diabetes mellitus

Abstract: Patients with type 2 diabetes mellitus (DM) are at a substantially increased risk of heart failure (HF) and HF mortality. Despite the lack of evidence that tight glycemic control reduces the incidence of cardiovascular (CV) events, a growing body of evidence suggests that the choice of glucose-lowering agents may influence outcomes including HF. Thiazolidinediones are associated with a significant risk of HF. For metformin, sulphonylureas and insulin, little data is available to indicate the impact on HF. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…The results of the primary outcome were driven by a reduction in non-fatal MI and stroke. However, in light of its smaller non-inferiority design, this trial may underestimate the difference in CV mortality compared with the much larger LEADER trial ( Asleh et al, 2018 ).…”
Section: Current Therapies: Novel Glucose-lowering Drugsmentioning
confidence: 99%
“…The results of the primary outcome were driven by a reduction in non-fatal MI and stroke. However, in light of its smaller non-inferiority design, this trial may underestimate the difference in CV mortality compared with the much larger LEADER trial ( Asleh et al, 2018 ).…”
Section: Current Therapies: Novel Glucose-lowering Drugsmentioning
confidence: 99%
“…Sulphonylureas have a higher incidence of cardiovascular adverse events compared to other hypoglycemic agents, and insulin sensitizers also significantly increase the risk of HF in T2DM patients. 63,64 Recently, SGLT2 inhibitors and GLP-1 agonists have been reported to have a significant reduction in cardiovascular mortality. [65][66][67] A growing number of studies have also shown that SGLT1 inhibition does have cardiovascular benefits.…”
Section: The Effects Of Sglt1 Inhibition On Diabetes-related Heart In...mentioning
confidence: 99%
“…The risk of heart failure in T2DM remains higher compared to non-DM (diabetes mellitus) individuals after adjustment for other risk factors such as serum cholesterol levels, hypertension, or coronary artery disease [ 50 , 51 ]. On the other hand, the presence of DM worsens prognosis in the heart failure population in which the mortality rates are significantly higher than in the non-DM population [ 52 ].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%